Equilateral Triangle Concept for Relocation of the Nipple in Breast Reduction - Ercan, Alp; Ercan, Leman Damla; Yalçın, Can Ege; Morkuzu, Suat (Cerrahpaşa Medical Journal, 2024)
Objective: Planning and marking are vital stages of breast reduction, and a significant step in this process is deciding the new location of the nipple. Many intricate measurements have been described to guide this decision, but there has not been a consensus on the best method. Most of these methods involve vertical repositioning of the nipple, and horizontal repositioning is neglected to some extent. Common marking techniques are not suitable for all breast types, especially breasts with laterally placed nipples. We propose a simple method for preventing mispositioning of the nipple– areola complex (NAC) on the horizontal axis. Methods: The suprasternal notch to nipple (SNN) axis was used to relocate the NAC in selected patients with laterally located nipples. During marking, both SNN axis and midclavicular point to nipple (breast meridian) axis were drawn. New potential nipple locations were reflected on both axes, and the distance in between was measured. Patients were asked to evaluate their post-op results regarding both shape and NAC positioning. Results: Seventeen patients with laterally placed nipples were operated on by the primary surgeon. The SNN axis was used to relocate NAC. The mean distance between two projected nipple locations was 2.1 cm. No major complications were encountered, and all the patients were satisfied with their appearance. Conclusion: The horizontal repositioning of the nipple during breast reduction is not given enough significance. While performing breast reduction, using the traditional breast meridian for patients with laterally placed nipples can lead to lateralized nipples after surgery. Our simple plan modification can prevent this minor complication. Cite this article as: Ercan A, Ercan LD, Yalçın CE, Morkuzu S. Equilateral triangle concept for relocation of the nipple in breast reduction. Cerrahpaşa Med J. 2024;48(1):50-54.